ChemInform Abstract: Simple Route to Multisubstituted Tetrahydropyrimidines. Issue 50 (December 2015) - Vincze, Zoltan; Pilipecz, Mihaly V.; Scheiber, Pal; Varga, Tamas R.; Toth, Gabor; Nemes, Peter
Abstract: Nitroenamines (I), (VI), and (VIII) serve as key intermediates in the synthesis of pyrrolopyrimidines (III), pyrimidines (IX) and dihydropyrrolones (XI).